Planning for the management of village-owned enterprises (BUMDes) : Perencanaan pengelolaan badan usaha milik desa (BUMDes) - Taufikur Rakhman, Antony; Fitria Agustina, Isna (Universitas Muhammadiyah Sidoarjo, 2022)
The weak understanding of BUMDes is what makes BUMDes discourse not well socialized to the villagers. How can you socialize if your own understanding is still very inadequate. As a result, the issue of BUMDes only blows on the village elite only or only in the village device circle. The weak development of human resources is what makes the institutional capacity and entrepreneurship of the village undeveloped and the lack of personnel to manage BUMDes MARGO JOYO in Semambung village jabon subdistrict and the thing that is no less important is most young people to work. It is still difficult to convince young people that BUMDes can guarantee harmony for its activists. The methods used qualitative descriptive data are obtained through observation, documentation, interviews and using the source of books, journals, and policy documents. The result of this research is that there are three processes of managing village-owned enterprises (BUMDes) namely planning which in planning there are 2 categories including work program plans that include making budget budgets to get capital and can open new business units. The second category in the planning is the acceptance target plan which includes socialization of Semambung Village residents to participate in the use of POS Indonesia services in electronic bill payment services.